Investigation of the relationship between semantic ınformation and verbal working memory in children with typical developing, down syndrome and autism spectrum disorder - Tüba KÜÇÜK DOĞAROĞLU; Funda Acarlar (My University, 2022)
The aim of this study is to investigate the relationship between semantic knowledge and verbal working memory (VWM) in children with typical development (TD), Down syndrome (DS) and autism spectrum disorder (ASD).Descriptive research and relational research methods were used in the design of the research.Children in the study group were matched with the Raven Colored Progressive Matrices Test according to their non-verbal intelligence score.The study group of the study consisted of 17 TD children aged 4-5 years and 14 DS and 15 ASD children whose nonverbal intelligence ages are between 4-5 years.Semantic knowledge was evaluated in the dimensions of vocabulary breath and vocabulary depth.The language sample collected in narrative context was used to evaluate of vocabulary breath. Vocabulary Depth Test (VDT) was used to assess vocabulary depth.VWM was assessed with the Nonsense Word Repetition Test (NWR).The results of the research revealed that all groups showed significant differences in vocabulary breadth, vocabulary depth and VWM performances.It was found that there was a significant and positive relationship between vocabulary breadth, vocabulary depth and VWM in all groups.VMW predicted vocabulary breadth and vocabulary depth in children with TD and DS.Vocabulary breadth was found to predict vocabulary depth in children with TD and ASD.However, VMW did not predict vocabulary breadth and depth in ASD.The results obtained from the study show that the results differ in the two different diagnostic groups.While the results were discussed regarding the contribution of verbal working memory in the acquisition of semantic knowledge in DS, the importance of word width in the acquisition of word depth in ASD was discussed. In addition, it has been suggested to examine different variables that may be effective in the development of semantic knowledge in both diagnostic groups.
Keywords: Semantic Knowledge; Vocabulary Breath; Vocabulary Depth; Down Syndrome; Autism Spectrum Disorderc